DESIGN OF MIXED USE BUILDING CIBADAK BUILDING BANDUNG - Khairunnisa, Shafira
Cibadak has always been one of the most bustling area in the city of Bandung, famous for its culinary festivities. Along with increasing growth population and interests in economic activities, it certainly has the potential to grow. However, due to the densely populated area and lack of space, it can be challenging to develop the area. A mixed use building is a concept in which the building has mixed functions to support more than one kind of activity, in this case as a shopping center and apartment. As an area prone to flood, the zero delta Q concept is implemented to ensure the project will not increase runoff discharge to nearby rivers. Therefore, the probability of flood can be prevented. In order to obtain the zero delta Q condition, water from rainfall collected from tower roofs and podiums are stored for later use. Hydrological analysis is done first to determine predicted discharge and flood discharge for certain return periods, which is then used to evaluate nearby river capacity and design drainage network, as well as reliable discharge to design rainwater harvesting and water supply methods. The scope of drainage network designed in this thesis consists of the tower’s roof, podiums for both apartment and commercial use, and the yard area. The layout of drainage network is done by dividing areas into several catchment areas, which are then used to calculate runoff discharge using rational methods. Drainage network components are designed based on the runoff discharge and also layout of the network. Then, the change in runoff that occur needs to be checked in order to make sure the zero delta Q concept is well implemented. To accommodate water needs, aside from water collected from rainfall, supply from PDAM is also needed. Then, water reservoirs are designed based on water demand and availabilty, both from rainfall and PDAM. The reservoirs consist of Ground Water Tank, located in the second basement of the building, and the Roof Water Tank, located on the roof of both towers. Furthermore, components supporting water distribution from GWT to RWT, such as pumps and pipes will also be designed.